2017
DOI: 10.1080/07359683.2017.1375236
|View full text |Cite
|
Sign up to set email alerts
|

How does objective and subjective human papillomavirus knowledge affect information-seeking intentions and source preferences?

Abstract: This study examines the effects of objective (factual information) and subjective knowledge (an individual's self-assessment of how much knowledge they have) on information-seeking intentions and source preferences. It explores the human papillomavirus (HPV) knowledge inequalities in groups of young adults age 18-26 years with and without vaccinations and diagnosis, and different demographics/socio-economic and perceptions of health status. Higher subjective HPV knowledge leads to greater information-seeking i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Objective knowledge is information stored by an individual in their long-term memory [ 25 ]. Subjective knowledge, in turn, refers to the self-perception of one’s own knowledge, and includes a level of confidence in an individual’s own perceived knowledge [ 27 , 28 ]. While it is reasonable to assume that people’s perception of their subjective knowledge strongly reflects their actual knowledge in a given domain, a lot of research has shown that people tend to overestimate it even in the contexts in which they are not educated or professionally engaged [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Objective knowledge is information stored by an individual in their long-term memory [ 25 ]. Subjective knowledge, in turn, refers to the self-perception of one’s own knowledge, and includes a level of confidence in an individual’s own perceived knowledge [ 27 , 28 ]. While it is reasonable to assume that people’s perception of their subjective knowledge strongly reflects their actual knowledge in a given domain, a lot of research has shown that people tend to overestimate it even in the contexts in which they are not educated or professionally engaged [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, research has identified subjective knowledge (an individual's self-assessment of the degree of knowledge they possess) as a crucial factor influencing users' selection of information sources. Manika et al. (2017) note that highly subjective knowledge leads people to prefer information from sources such as family, friends and mass media and rarely from professionals and the internet.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, research has identified subjective knowledge (an individual's selfassessment of the degree of knowledge they possess) as a crucial factor influencing users' selection of information sources. Manika et al (2017) note that highly subjective knowledge leads people to prefer information from sources such as family, friends and mass media and rarely from professionals and the internet. In a study on health information-seeking behavior, Zimmerman (2021) found that there was a positive relationship between users' information literacy and the quality of the selected information sources.…”
Section: Context Of Information Source Preferences Researchmentioning
confidence: 99%
“…High-risk perceivers may seek information and educate themselves about the virus and available preventive measures. 44,45 This emphasizes the importance of risk perception in driving information-seeking behaviors and the potential for increased knowledge to translate into more informed decisions regarding HPV vaccination.…”
Section: Discussionmentioning
confidence: 99%